Pelaksanaan Kegiatan Diklat Pemasaran Digital Memberi Pengaruh Baik dalam Pengabdian Kepada Masyarakat (PKM) di Desa Purba Dolok - Samuel Nababan; Christian Rosen Sitorus; Maris Simbolon; Ningsih Pandiangan; Radot Paulina Manalu (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Digital marketing is a skill that many people really need to learn in order to increase their knowledge and prepare themselves for a successful career in the future, increase creativity and be innovative. In an effort to increase national knowledge, one of the activities that students need to carry out is KPPM which is an activity that focuses on community service. This type of research uses a descriptive qualitative research method which is used to research and describe the positive influence on the implementation of training activities carried out by IAKN Tarutung students in Purba Dolok village, namely KKN in the form of PKM. So this type of research is also based on factual data and field data, where the researcher goes directly into the field to see directly the conditions that are the subject of the research. As a result of the training activities that have been carried out, it can be concluded that the participants can understand the material presented by the resource person and also increase the insight and knowledge of the training participants.